2003
DOI: 10.1073/pnas.2136685100
|View full text |Cite
|
Sign up to set email alerts
|

An approach to genomewide screens of expressed small interfering RNAs in mammalian cells

Abstract: To facilitate the construction of large genomewide libraries of small interfering RNAs (siRNAs), we have developed a dual promoter system (pDual) in which a synthetic DNA encoding a genespecific siRNA sequence is inserted between two different opposing polymerase III promoters, the mouse U6 and human H1 promoters. Upon transfection into mammalian cells, the sense and antisense strands of the duplex are transcribed by these two opposing promoters from the same template, resulting in a siRNA duplex with a uridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 36 publications
(31 reference statements)
2
133
0
1
Order By: Relevance
“…Instead of generating large libraries of chemically synthesized siRNAs, several investigators have created their own large-scale shRNA or siRNA libraries encoded by plasmid vectors and used these libraries to identify new genes involved in the p53 pathway 33 , human proteasome function 34 and the NF-κB signaling pathway 35 . These screens demonstrate the utility of large RNAi screens in mammalian cells but also underscore the need for better siRNA and shRNA selection methods because many RNAi constructs that should have elicited effects did not 35 . A development that may help with this issue is the use of endonuclease-prepared siRNAs, siRNAs that are generated by the RNase III-mediated degradation of long dsRNAs 36 .…”
Section: High-throughput Rnai Screens In Cultured Cellsmentioning
confidence: 99%
“…Instead of generating large libraries of chemically synthesized siRNAs, several investigators have created their own large-scale shRNA or siRNA libraries encoded by plasmid vectors and used these libraries to identify new genes involved in the p53 pathway 33 , human proteasome function 34 and the NF-κB signaling pathway 35 . These screens demonstrate the utility of large RNAi screens in mammalian cells but also underscore the need for better siRNA and shRNA selection methods because many RNAi constructs that should have elicited effects did not 35 . A development that may help with this issue is the use of endonuclease-prepared siRNAs, siRNAs that are generated by the RNase III-mediated degradation of long dsRNAs 36 .…”
Section: High-throughput Rnai Screens In Cultured Cellsmentioning
confidence: 99%
“…59,60 In those studies, sets of arrayed expression libraries from chemically synthesized oligonucleotides which target 7914 and 9610 different human genes, respectively, were produced. 59,60 Other approaches for large-scale genome-wide screening using RNAi, which involve generating a library of polymerase chain reaction products that encode shRNAs 61 and constructing random shRNA libraries based on manipulation of complementary or genomic DNA, [62][63][64] have also been reported recently. RNAi using genome-wide libraries is expected to complement current experiments that aim to functionally map the mouse genome by chemical or insertional mutagenesis.…”
Section: Short Rna-mediated Rnai In Mammalian Cellsmentioning
confidence: 99%
“…Initial proof of concept for RNAi screening using both synthetic siRNAs and plasmid-encoded shRNAs were reported last year using gene-family focused libraries Brummelkamp et al, 2003). In rapid succession, Zheng et al (2004) reported a PCR-based approach to generate a DNA-mediated RNAi library representing >8000 human genes and Berns et al (2004) described the construction and application of a retroviral library encoding shRNAs covering 7194 targets. Finally, Paddison et al (2004) reported the creation of a retroviral library encoding shRNAs targeted against 10 000 human and 5000 mouse genes.…”
Section: Rnai As a Screening Toolmentioning
confidence: 99%
“…In addition, no selection is required and both activators and repressors can be detected in the same experiment. This format has been used successfully in both RNA-and DNA-based screens Zheng et al, 2004). However, this format requires considerable up-front effort, including the design, synthesis and arraying of the individual reagents.…”
Section: Selecting the Screening Formatmentioning
confidence: 99%